Whole Genome Sequence Analysis Reveals Lower Diversity and Frequency of Acquired Antimicrobial Resistance (AMR) Genes in E. coli From Dairy Herds Compared With Human Isolates From the Same Region of Central Zambia - Mainda, Geoffrey; Lupolova, Nadejda; Sikakwa, Linda; Richardson, Emily; Bessell, Paul R.; Malama, Sydney K.; Kwenda, Geoffrey; Stevens, Mark P.; Bronsvoort, Barend M. deC.; Muma, John B.; Gally, David L. (Frontiers in Microbiology, 2019)
Antibiotic treatment of sick dairy cattle is critical for the sustainability of this production system which is vital for food security and societal prosperity in many low and middle-income countries. Given the increasingly high levels of antibiotic resistance worldwide and the challenge this presents for the treatment of bacterial infections, the rational use of antibiotics in humans and animals has been emphatically recommended in the spirit of a ‘One Health’ approach. The aim of this study was to characterise antimicrobial resistance (AMR) genes and their frequencies from whole genome sequences of E. coli isolated from both dairy cattle and human patients in central Zambia. Whole genome sequences of E. coli isolates from dairy cattle (n=224) and from patients at a local hospital (n=73) were compared for the presence of acquired AMR genes. In addition we analysed the publicly-available genomes of 317 human E. coli isolates from over the wider African continent. Both acquired antibiotic resistance genes and phylogroups were identified from de novo assemblies and SNP based phylogenetic analyses were used to visualise the distribution of resistance genes in E. coli isolates from the two hosts. Greater acquired AMR gene diversity was detected in human compared to bovine E. coli isolates across multiple classes of antibiotics with particular resistance genes for extended-spectrum beta lactamases (ESBL), quinolones, macrolides and fosfomycin only detected in E. coli genomes of human origin. The striking difference was that the Zambian or wider African human isolates were significantly more likely to possess multiple acquired AMR genes compared to the Zambian dairy cattle isolates. The median number of resistance genes in the Zambian cattle cohort was 0 (0-1 interquartile range), while in the Zambian human and wider African cohorts the medians and interquartile ranges were 6 (4-9) and 6 (0-8) respectively. The lower frequency and reduced diversity of acquired AMR genes in the dairy cattle isolates is concordant with relatively limited antibiotic use that we have documented in this region, especially among smallholder farmers. The relatively distinct resistant profiles in the two host populations also indicates limited sharing of strains or genes.